A rabbit technology to control coccidiosis - Finzi A.; Mordacchini Alfani M.L. (Rabbit production in hot climates, 1994)
A system of movable cages which, when they are displaced on the pasture, can break the biological cycle of coccidia was studied. Weaned rabbits, 35 days old, where set in groups of seven in movable cages. These had a surface of 1 sqm and were provided of feed and water ad libitum. The rabbits of one cage received robenidine 66 ppm; two more groups received the same feed without robenidine. The cages, disposed on the turf, were displaced every day. The trial was repeated in spring and late autumn. The oocysts were counted in the feces the first day of the trial, then after two and four weeks, always the very day they were excreted, to test the effect of cage displacement. The oocysts were also counted each three days in the place where they were excreted to test the effect of permanence on the ground. After four weeks the rabbits not receiving robenidine eliminated 55 less oocysts than at beginning, showing the effectiveness of the system which can be very useful in rural areas of developing countries where the use of coccidiostats is nearly impossible. The number of oocysts decreased quickly in the feces on the ground; after one week they were reduced to 44 of the original amount, and after one month only few oocysts were detectable.
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)